Gender Discrimination on Child Marriage in Indonesia: A Quantitative Research Using Bootstrap Approach - Ade Dedi Rohayana (Muwazah, 2020)
The main objective of this study is to analyze gender discrimination in child marriage in Indonesia. The discrimination is based on early marriage, namely Indonesian youth aged 20-24 years who have been married before the age of 19 years. There are two main factors used, namely gender and age groups. The age group represents the age at first marriage for Indonesian youth who are categorized as early marriage, namely the group aged less than 15 years and aged in the group 16-18 years. This study applies a bootstrap approach to the analysis of variance (ANOVA) due to the failure of the initial assumption tests on the original data. The analysis results show there are significant differences between male and female youth in the percentage of child marriage cases. Gender inequality is indicated based on the finding that young women are found to be four times more vulnerable to being trapped in child marriage than boys. In addition, the results of the analysis also indicate that young women are easier to get trapped in child marriage practices for both age groups. Furthermore, the results of the analysis also indicate that young women are more prone to be involved in child marriage when they are in the 16-18 year group.